"It’s Your Breath in Our Lungs": Sean Feucht’s Praise and Worship Music Protests and the Theological Problem of Pandemic Response in the U.S. - Perez, Adam A. (Religions, 2022)
In response to U.S. government restrictions imposed as part of a nationwide response to the COVID-19 pandemic, charismatic worship leader Sean Feucht began a series of worship concerts. Feucht positioned these protests as expressions of Christian religious freedom in opposition to mandated church closings and a perceived double-standard regarding the large gatherings of protesters over police violence against Black and Brown persons. Government restrictions challenged the sine qua non liturgical act of encounter with God for evangelicals, Pentecostals, and Charismatics: congregational singing in Praise and Worship. However, as Feucht’s itinerant worship concerts traversed urban spaces across the U.S. to protest these restrictions, the events gained a double valence. Feucht and event attendees sought to channel God’s power through musical worship to overturn government mandates and, along the way, they invoked longstanding social and racial prejudices toward urban spaces. In this essay, I argue that Feucht’s events reveal complex theological motivations that weave together liturgical-theological, social, and political concerns. Deciphering this complex tapestry requires a review of both the history of evangelical engagement with urban spaces and the theological history of Praise and Worship. Together, these two sets of historical resources generate a useful frame for considering how Feucht, as a charismatic musical worship leader, attempts to wield spiritual power through musical praise to change political situations and the social conditions.